Climate Change, Salinization and High-Yield Rice Production in Coastal Bangladesh. (23rd November 2017) - Dasgupta, Susmita; Hossain, Md. Moqbul; Huq, Mainul; Wheeler, David
Abstract : Progressive salinization of water and soil will be increasingly severe in low-lying coastal areas as climate change proceeds. Thus, understanding the economic impacts of salinity intrusion will be essential for effective adaptation planning. This paper uses econometric analysis to predict the impact of climate-induced increases in soil salinity on high-yielding-variety rice production in coastal Bangladesh. Findings indicate an output decline of 15.6 percent in nine subdistricts where soil salinity will exceed 4 deciSiemens per meter before 2050. Without new adaptation strategies, the predicted changes will result in 7.7 and 5.6 percent losses in the Barisal and Chittagong regions, respectively.